2000
DOI: 10.1063/1.1311833
|View full text |Cite
|
Sign up to set email alerts
|

Phonon mediated lifetimes in intersubband terahertz lasers

Abstract: We present a detailed study of the electron-LO phonon interaction in a triple quantum well structure, which acts as the active region in an intersubband terahertz emitter. The phonon modes of the heterostructure were calculated using a transfer matrix method within the framework of the dielectric continuum model. Unlike earlier calculations that approximate phonon emission rates using bulk-like phonon modes, we exploit the presence of specific interface and layer-confined phonon modes. The electronic levels ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…To obtain the IF dispersions in a MQW QCL, the isolatedstage boundary condition (BC) is generally assumed [7,11,13] (c N,+ = 0 and c N ,− = 0). However, this assumption leads to a discontinuity in the phonon potentials at the interfaces between adjacent stages [18], The IF potential in one stage (e.g., stage λ) is the combination of Φ i (q, z) in each region R i of the same stage, i.e., Φ λ (q, z) = Φ i (q, z), z ∈ R i .…”
Section: Phonon Confinementmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain the IF dispersions in a MQW QCL, the isolatedstage boundary condition (BC) is generally assumed [7,11,13] (c N,+ = 0 and c N ,− = 0). However, this assumption leads to a discontinuity in the phonon potentials at the interfaces between adjacent stages [18], The IF potential in one stage (e.g., stage λ) is the combination of Φ i (q, z) in each region R i of the same stage, i.e., Φ λ (q, z) = Φ i (q, z), z ∈ R i .…”
Section: Phonon Confinementmentioning
confidence: 99%
“…The phonon quantization was included in the Monte Carlo simulation [8,9] of a superlattice QCL with each period containing one barrier and one well, and an enhancement in the electron-LO phonon scattering rates was obtained. On the other hand, several groups [10][11][12] argued that the phonon confinement could significantly increase the scattering rates in MQW structures, but so far there has been no systematic account of phonon confinement in transport simulations of MQW QCLs.…”
mentioning
confidence: 98%
“…Moreover, Rücker et al 14 and Lee et al 36 showed that the DC model accurately predicts the total scattering rates obtained by microscopic calculations. In view of the accuracy of the DC model in the scattering rate calculation and the simplicity of its implementation, the DC model has been widely used [16][17][18]22,27,37 to treat phonon confinement in MQW structures.…”
Section: Phonon Confinement Modelingmentioning
confidence: 99%
“…15 Williams and Hu 16 also showed that the total phonon scattering rates including confinement in one stage ͑three quantum wells͒ of two GaAs/ Al 0.3 Ga 0.7 As terahertz QCLs are very close to those obtained using GaAs bulk phonons, thanks to wide wells and thin low-Al barriers. On the other hand, calculations by Menon et al 17 indicated that the scattering rate 21 ͑levels 2 to 1͒ in a similar three-QW ͑quantum well͒ THz structure can be strongly enhanced due to phonon confinement, and Ref. 18 reported that, in step quantum-well structures using GaAs/ Al 0.25 Ga 0.75 As/ Al 0.4 Ga 0.6 As materials, the scattering rates with phonon quantization are more than an order of magnitude greater than the bulk GaAs rate.…”
Section: Introductionmentioning
confidence: 95%
“…[25][26][27] These calculations do not consider screening, however, which tends to decrease the scattering rates.…”
Section: B Numerical Aspectsmentioning
confidence: 99%